A single-layer Janus membrane with dual gradient conical micropore arrays for self-driving fog collection. Issue 35 (23rd August 2017) - Ren, Feifei; Li, Guoqiang; Zhang, Zhen; Zhang, Xuedong; Fan, Hua; Zhou, Chen; Wang, Yulong; Zhang, Yinghui; Wang, Chaowei; Mu, Kai; Su, Yahui; Wu, Dong
Abstract : Inspired by natural creatures, the development of a device that collects water from fog represents an important research direction. Abstract : Inspired by natural creatures, the development of a device that collects water from fog represents an important research direction. However, present methods suffer from low efficiency, complex processes, expensive materials, etc. In this study, a single-layer hydrophilic/hydrophobic heterogeneous Janus aluminum membrane based on dual gradient conical micropore arrays is designed and fabricated by laser drilling and subsequent low surface energy modification. The droplets can automatically pass through the conical micropores on the Janus membrane, which results from the wetting driving force of gradient surface energy and the Laplace pressure of the conical morphology. Compared to the superhydrophilic membranes, the Janus membrane possesses a 209% enhancement in the water collection efficiency. This new type of self-driving water collection membrane may offer a way to construct an efficient fog collection system to relieve the freshwater crisis.